Endoscope-Assisted Microsurgical Removal of an Optic Foramen Meningioma through a Frontolateral Minicraniotomy - Kurucz, Peter; Opitz, Holger; Buchfelder, Michael; Ganslandt, Oliver (Journal of Neurological Surgery Part B: Skull Base, 2018)
A 72-year-old male patient with visual disturbance of the right eye was diagnosed with a small meningioma of the right optic foramen extending to the carotid cistern. The operation was performed through an individually tailored frontolateral minicraniotomy via a curvilinear skin incision behind the hairline. Endoscope-assisted microsurgical technique was used to resect the lesion. The roof of the optic canal was partly removed to get access to the intraforaminal tumor parts. The lesion could be completely removed and the patient showed a satisfactory visual recovery in the follow-up examinations. The link to the video can be found at: https://youtu.be/p8EZx7aryeQ .
EVALuna2:214806